Operating Room Noise and Team Communication during Facial Plastic and Reconstructive Surgery: A Multicenter Study - Levin, Marc; Brace, Matthew; Sommer, Doron D.; Roskies, Michael (Facial Plastic Surgery, 2022)
Operating room (OR) noise contributes to team miscommunication. In facial plastic and reconstructive surgery (FPRS), many cases are completed under sedation. This creates a unique environment wherein patients are aware of OR noise. The objectives of this study were to quantify noise and evaluate team members' perspectives on communication inside of FPRS ORs. This study was completed across three surgical institutions. Objective noise measurements were recorded with SoundMeter X. A communication questionnaire was delivered to OR team members following each case. Four hundred and twenty-three noise measurements were recorded during facelift/neck, eye/brow, rhinoplasty, and fat transfer/lip surgeries. The mean and maximum noise levels were 66.1 dB (dB) and 87.6 dB, respectively. Measurements during cases with general anesthetic (221/423, 52.2%) had higher noise measurements (70.3 dB) compared with those with sedation (202/423, 47.8%) (69.7 dB) (p = 0.04). The OR was louder with suction on (72.3 dB) versus off (69.3 dB) (p <0.00). Suction (34.5%) and music (22.4%) were the largest noise contributors according to questionnaire replies. Intraoperative noise, awake patients, and suctions/music may negatively impact FPRS OR communication. Innovation to improve FPRS intraoperative communication should be considered for effective patient care.
Keywords: OR noise; HVAC; OR communication; personal protective equipment; facial plastic and reconstructive surgery